(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the clinical, paraclinical characteristics and treatment outcomes of acute drug poisoning at the Emergency Department of Transport Hospital. Methods: A retrospective cross-sectional study was conducted on 48 patients aged ≥18 years admitted between January 2022 and September 2023. Variables included demographics, type of toxic agents, clinical manifestations, laboratory results, electrocardiographic abnormalities, management strategies, and discharge outcomes. Data were analyzed using SPSS 20.0 with statistical significance set at p<0.05. Results: The median age was 27 years, with the 18–29 age group accounting for 41.7%. More than 60% of patients were admitted within the first 6 hours. Paracetamol was the most common toxic agent (22.9%), predominantly associated with intentional self-poisoning. Common findings included tachyarrhythmia, electrolyte and acid–base disturbances, with elevated lactate observed in 34.5% of patients. ECG abnormalities included sinus tachycardia (31.3%), QT prolongation (12.5%), and QRS widening (14.6%). The mean hospital stay was 3 days; 93.8% of patients fully recovered, with no deaths reported. Conclusion: Acute drug poisoning at Transport Hospital predominantly affects young adults, most commonly due to paracetamol-related suicide attempts. Early diagnosis, timely intervention, and psychosocial support are essential to improve prognosis and prevent recurrence.